THE TRANSFORMATION OF INITIATIONS TO THE BUTT OF UNGUL EDUCATION WITH THE UNDERSTANDED CURRICULUM - Sholeh, Hindun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the impact of leadership transformation in efforts to achieve superior educational quality through the implementation of an independent curriculum. The focus of the research is on changes in leadership style, managerial strategies, and adaptation to the independent curriculum at Darul Hikmah Vocational School. The research method uses a qualitative approach with in-depth interviews with school leaders, teachers and educational staff. The research results show that leadership transformation has a crucial role in forming an organizational culture that supports the implementation of the independent curriculum. innovative learning environment. In addition, it was found that collaboration between leaders and educational staff was the key to success in implementing the independent curriculum. The implications of these findings stimulate the need for leadership development that is adaptive and responsive to contextual changes, especially in facing the dynamics of an independent curriculum. The place of research was carried out at the Darul Hikmah Paiton Vocational School, Probolinggo. Based on the research results, several results show, including (1) Changes in Leadership Style: School leaders experienced changes in their leadership style, switching from a traditional model to a transformational model. (2) Adaptation to the Independent Curriculum: Identify leaders' strategies for integrating independent curriculum principles in planning and teaching. This research contributes to the understanding of how leadership transformation can be a driver of superior educational quality in the era of the independent curriculum.